Artificial Intelligence and the Future of Teaching in Higher Education at A’Sharqiyah University (ASU) in Oman - Matari, Ali Said Al; Mukit, Abdul; Saadi, Saliha Al; Balushi, Wasan AL; Al-Abri, Juhaina Suliman (DPPM Universitas Pelita Bangsa, 2023)
The study aimed to identify artificial intelligence and the future of teaching in higher education institutions represented by the University of A'Sharqiyah in the Sultanate of Oman as a model, and the researchers used the qualitative approach, through an interview with (4) technologically capable teachers who have experience in employing artificial intelligence in teaching, and the aim of the interview was to answer (3) open questions: How can artificial intelligence be used to enhance education and the quality of the teacher's daily work? How can we as teachers ensure ethical and inclusive work? The results showed that AI (Artificial Intelligence) can be used to personalize learning, automate grading, provide virtual assistance, and analyze data. However, there was less agreement on how AI can be leveraged to enhance education. For example, only 75% of people agreed that AI can be used to provide assistive technologies, and only 50% of people agreed that AI can be used to discover and curate resources. Overall, the answers suggest that ensuring the ethical, inclusive, and equitable use of AI in teaching requires a combination of awareness of potential biases, transparency, and monitoring, as well as education about AI ethics and advocacy for ethical AI in education. The researchers recommended a set of recommendations, the most important of which are: Emphasizing the importance of employing artificial intelligence in teaching and considering the ethical aspects regulating the application of artificial intelligence in teaching.